2017
DOI: 10.2139/ssrn.3266607
|View full text |Cite
|
Sign up to set email alerts
|

Who Gives? On Empathy and Impulsiveness

Abstract: We investigate the impact of empathy and impulsiveness on charitable giving using a real donation experiment. We confirm that greater empathy predicts greater charitable giving. Contrary to recent literature, however, we find a significant negative relationship between impulsiveness and donation behavior. Specifically, when financial resources are scarce, donations are more often made by decision-makers who are able to suppress an intuitively egoistic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…Estimation results show that more empathetic consumers will bid more, indicating empathy as a motivation behind anti‐poverty behaviour. This is consistent with literature that finds a positive relationship between empathy and charity donation (Andreoni et al, 2018). Keeping other variables constant, people who think that anti‐poverty products generally are higher quality are willing to pay 0.52 RMB more than those who do not, which implies that product quality is one important factor to maintain efficiency in the anti‐poverty product market.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Estimation results show that more empathetic consumers will bid more, indicating empathy as a motivation behind anti‐poverty behaviour. This is consistent with literature that finds a positive relationship between empathy and charity donation (Andreoni et al, 2018). Keeping other variables constant, people who think that anti‐poverty products generally are higher quality are willing to pay 0.52 RMB more than those who do not, which implies that product quality is one important factor to maintain efficiency in the anti‐poverty product market.…”
Section: Resultssupporting
confidence: 93%
“…The details of the auction process are given in the Online Appendix. Besides demographics and perception variables, literature has shown that personality traits such as empathy (Andreoni et al, 2018) and past‐prosocial experiences (Aknin et al, 2018) can also influence prosocial behaviour or ethical consumption. Questions about these factors were asked after the auction experiment and used for heterogeneous analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been argued that impulsiveness plays a central role in the online donation context, which is similar to an online shopping context. Although prior literature in donation has already noticed that impulsiveness of donors plays an essential role in shaping the donation decision (Andreoni et al. , 2018; Bennett, 2009), they mainly focused on its direct effect on behavioral intention and whether the personal impulsiveness would amplify or mitigate the effects of motivational factors on behavioral intention (e.g.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Personal impulsiveness is influential on online user behavior, including online donation. Prior studies have investigated the personal impulsiveness's direct effect on intention to donate as well as the moderating role of impulsiveness in other contexts such online shopping (Andreoni et al. , 2018; Lee and Yi, 2008); however, limited attention has been paid to its moderating roles in charity donation.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Previous studies have reported that the significance of self-control for explaining donation among adults. 31 , 32 Moreover, a field experiment for children aged between 4–8 found that self-control resources depletion led to significantly lower likelihood of donating. 33 However, few studies have explored the relationship between self-control ability and donation behavior.…”
Section: Introductionmentioning
confidence: 99%